(untitled) (The Research of Medical Science Review, 2025)
Background: The second most common bacterial cause of diarrhea in infants and children is urinary tract infection (UTI). The estimated incidence of urinary tract infections in children is 3–10% for female and 1-3% for male. Renal parenchymal damage and renal scarring are permanent consequences of Urinary tract infection that can lead to hypertension and progressive renal impairment. Objective: The aim of this study was to appraise the incidence of Urinary tract infection in children presenting diarrhea. Materials and Methods: This cross-sectional study was conducted by women and children hospital karak for six months duration from July 2024 to December 2024. A total of 140 patients, both male and female, ranging in age from 7 months to 5 years, were included in the study. Children older than five, those with a history of using antibiotics within 48 hours, and those without approval were not allowed to participate in this study. Urinary catheterization was used to investigate the urine culture. All of the patients' indications and symptoms were recorded, and urine was sent to a reputable lab for culture. SPSS 24.0 was used to analyze all of the data. Results: The study included 140 cases of diarrhea that were admitted to the pediatric ward. Out of 140 patients 95 (67.8%) were male patients and 45 (32.1%) were female. Age of 35 (25%) patients were from 7 months to 1 years, 60 (42.1%) had ages between 2 to 3 years and 45 (32.1%) were from 4 to 5 years. Furthermore, 45 (32.1%) patients experienced mild diarrhea, 65 (46.6%) had moderate diarrhea, and 30 (21.4%) had severe diarrhea. Of the 140 patients, Urinary tract infection (UTI) was not observed in 90 (64.2%) patients while 50 (35.7%) patients were observed with UTI. E.Coli (25 cases) and Enterococcus (15 cases) were the most frequently isolated organisms from urine, followed by Klebseilla (7 cases) and citrobacter (3 cases). Conclusion: For infants and children, diarrhea is the most prevalent problem. It is linked to a higher rate of morbidity and mortality in children older than three years. It is concluded that children who arrive with diarrhea had a higher prevalence of urinary tract infections. In this study E.coli was the most prevalent pathogen followed by Enterococus. When a child has diarrhea, a urine analysis and culture are necessary to confirm a urinary tract infection and avoid long-term consequences such hypertension and renal parenchymal damage.